"Doing what it takes to keep the school open": The philanthropic networks of progressive charter schools - Elise Castillo (Arizona State University, 2020)
Researchers have demonstrated how venture philanthropic networks advance the growth of charter schools underpinned by market tenets. However, little remains known about how progressive charter schools mobilize financial support when most funding from philanthropic networks flows to market-oriented charters. This qualitative study examines how three progressive charter schools in New York City mobilized financial support, the extent to which charters' financial supporters operated in a networked context, and the extent to which charters' resource mobilization activities reflected their founding progressive tenets. Findings reveal that the focal charters incorporated market logic when cultivating financial support networks. In doing so, schools endeavored to secure their own resource advantages while reinforcing resource inequities across New York City's unequal educational landscape, hence undermining the equity and community responsibility dimensions of their progressive missions.